If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2x + 1) = 1 + -4(x + 9) Reorder the terms: -5(1 + 2x) = 1 + -4(x + 9) (1 * -5 + 2x * -5) = 1 + -4(x + 9) (-5 + -10x) = 1 + -4(x + 9) Reorder the terms: -5 + -10x = 1 + -4(9 + x) -5 + -10x = 1 + (9 * -4 + x * -4) -5 + -10x = 1 + (-36 + -4x) Combine like terms: 1 + -36 = -35 -5 + -10x = -35 + -4x Solving -5 + -10x = -35 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -5 + -10x + 4x = -35 + -4x + 4x Combine like terms: -10x + 4x = -6x -5 + -6x = -35 + -4x + 4x Combine like terms: -4x + 4x = 0 -5 + -6x = -35 + 0 -5 + -6x = -35 Add '5' to each side of the equation. -5 + 5 + -6x = -35 + 5 Combine like terms: -5 + 5 = 0 0 + -6x = -35 + 5 -6x = -35 + 5 Combine like terms: -35 + 5 = -30 -6x = -30 Divide each side by '-6'. x = 5 Simplifying x = 5
| (x-5)(2x^2+3x-1)= | | 3(x+9)=42 | | X^6+5x^3-6=0 | | x(x)+5x+6=0 | | x(x)-5x-6=0 | | (3x^2-4x+10)-(x^2-9x+13)= | | c+150=1860 | | 5x(x)=6+2x | | x-13=-3 | | (2x^2-x+7)+(3x^2+x-9)= | | x(x)-7x-8=0 | | (40x)+(20*1.5x)=1625 | | 2-4y=4-5y | | 7y+3=6y-2 | | 6.4-2.1x=-77.4 | | x+y^2=0 | | 5-5x+8+2x+4x-4=3+2*5 | | x=1-y^2 | | 48=12-6n | | -2.3+m=-2.3 | | x-3/2=7/4 | | r+3.5=8 | | m(m)+6m-9=0 | | 20=10-5p | | 3(x)(x)-2x-5=0 | | (5x-5)(5x-5)= | | 15-39=-9 | | (7x^3-9x^2+5x)-(2x^2+3+6)= | | 2(x)(x)-3x-8=0 | | 40*12x=60x | | 25=7+3x | | 36x^2-12x+2=0 |